Comparison of GC-MS, HPLC-MS and SIFT-MS in conjunction with multivariate classification for the diagnosis of Crohn's disease in urine1. Issue 19 (7th October 2015) - Cauchi, M.; Fowler, D. P.; Walton, C.; Turner, C.; Waring, R. H.; Ramsden, D. B.; Hunter, J. O.; Teale, P.; Cole, J. A.; Bessant, C.
<x xml:space="preserve">Abstract</x> The developed world has seen an alarming increase in the incidence of gastrointestinal diseases, among the most common of which is Crohn's disease (CD) in the young.